STUDIES ON ANTIFUNGAL ACTIVITY OF A BACTERIAL STRAIN ON SOME FOOD SPOILAGE FUNGUS - DIPTENDU SARKAR,; SOMA CHAKI, (International Journal of Pharma and Bio Sciences, 2013)
Due to the development of increased resistance power of large number of fungal and bacterial pathogens to common antimicrobial agents, there is an urgent need to survey for new novel antimicrobial agents. In the present study the bacterial strain capable of producing antimicrobial agent was isolated from soil collected from the organic waste dump site. The isolated bacterial strain was further screened for their antifungal activity. The identified antifungal bacteria were Azomonas sp. DS. The metabolites of the isolated bacteria were screened for antifungal activity against ten different fungal species. Screening was done by using paper disc containing 20µl of culture supernatant placed on nutrient agar plate seeded with test organisms. The activity was determined by measuring the inhibition zone diameter (in cm) both for crude and dilution with 0.1 (M) phosphate buffer (pH-7.0) in the ratio of 1:1 (Crude extract:Buffer) . The Azomonas sp. DS showed inhibition zone diameter of 6.3 cm against Beauveria sp. with the application of crude metabolite and dilution of crude metabolite with 0.1 (M) phosphate buffer (pH-7.0) in the ratio of 1:1 (Crude metabolite: Buffer) showed inhibition zone diameter of 4.0 cm. From this work it might be concluded that Azomonas sp. DS can be used for the production of novel antifungal agent. Further study will be needed for characterization of the metabolites.